(untitled) (Herald of Journalism, 2020)
The topic of mass media coverage of terrorism is relevant in terms of the frequency and magnitude of terrorist acts taking place around the world. Publications on this issue are numerous, but all studies focus on the fact that terrorists use means of communication in order to publicize their illegal acts and attract attention from the state and society. The development of the Internet, to which all previously used analogue mechanisms and principles of monitoring the information environment prove to be inapplicable, has enriched terrorists with an extremely powerful tool for promoting their views and mobilizing like-minded people. Extremist materials published on Internet resources are becoming readily available to a wide audience, despite the ongoing work to block these sources. Most online videos, audio recordings and texts of extremist content propagate the activities of terrorists. The aim of this article is the analysis of terrorism as a special type of communication, which destructively affects the public consciousness and social institutions. The scientific significance of the article is determined by the study of the interaction of communication processes with the phenomenon of terrorism, in particular the role of the media in assessing acts of terror. The research methodology provides a systematic approach, a method of selection, analysis. The result of the research is to determine the informational aspect of modern terrorism, its concept and strategy. The latest information technology, the development of social networks can enhance the impact of terrorism on society, which determines the scientific value of this article. Practical significance lies in the possibility of introducing research results into the process of training at the faculties of journalism at universities of the Republic of Kazakhstan in specialized and elective disciplines, in conducting special courses for journalists, PR specialists, political scientists covering issues of extremism and terrorism, as well as special services in matters of interaction with funds mass media.